Utricularia uxoris (Lentibulariaceae), una nueva especie costarricense de la Sect. Orchidioides - Gómez-Laurito, Jorge (2015)
A new species of Utricularia (Lentibulariaceae) sect. Orchidioides is described and illustrated in this paper. U. uxoris is distinguished by its small, delicate habit, and tiny, glabrous, green flowers with a white spur.